Structural behaviour of hardwood veneer-based circular hollow sections of different compactness. (10th May 2018) - Gilbert, Benoit P.; Underhill, Ian D.; Fernando, Dilum; Bailleres, Henri; Miller, Dane
Highlights: Veneer-based timber compact and slender cross-sectional shapes are investigated. The sections were tested in bending, shear and compression. Bending: sudden failure of the slender sections compression fibre is observed. Shear: all cross-sections have similar and relatively low shear strength. Compression: the compact sections were ductile, the slender ones burst into strips. Abstract: This paper presents the capacity and structural behaviour of hardwood veneer-based circular hollow sections (CHS) tested in bending, shear and compression. The sections were manufactured from early to mid-rotation (juvenile) Gympie messmate ( Eucalyptus cloeziana ) plantation thinned logs. In total twenty-one 167 mm Outside Diameter (OD) × 1.2 m long CHS were manufactured in seven sets of three nominally identical sections. Two different wall thicknesses were investigated to produce nine compact and twelve more slender cross-sections. The sections were also manufactured in three different structural grades. A sudden failure mode was observed in the compression zone of the slender sections tested in bending. In compression, the compact sections showed a ductile behaviour, while the slender sections showed a more brittle behaviour, with the sections bursting into longitudinal strips. While a relationship was observed between the bending and compressive capacities, and the structural grade, no such relationship was noticed for the shear capacity. Comparison to steel and concrete sections of similar outside diameter proved that the timber sections are the most efficient in terms of bending and compressive capacity to linear weight ratio. The timber sections fall behind their steel and concrete counterparts in terms of shear efficiency, however they still have enough shear capacity for representative structural applications.